¿Por qué luchamos? : un libro sobre el amor y la libertad - D'Ávila, Manuela (Feminismos latinoamericanos, 2020)
Manuela D'Avila explains current feminism for those who still do not know or understand it. With her it is possible to understand that feminism is a matter for everyone. It is a book dedicated especially to young women who want to commit or want to know more and do not dare to ask. It is also a conversation, a hug and a point of support to reflect on motherhood and sisterhood, differences and equality, deconstruction and freedom, domestic violence and fear, in short: everything for which we fight The author suggests but also interacts with the readers, encourages the meeting, the brotherhood and listening to make sure (and make sure) that women will never be alone again.